Oxide solid electrolyte, preparation method thereof and all-solid-state battery
By performing multi-ion co-doping synergistic action in the oxide solid electrolyte, the lattice structure is optimized, and the problem of low ion conductivity of existing oxide solid electrolytes is solved, and high ion conductivity at room temperature is achieved.
Patent Information
- Application Number
- CN202510010604.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
During the preparation process, existing oxide solid electrolytes face problems such as unsatisfactory phase purity, low sintering activity, high production cost and low ionic conductivity.
The lattice structure is optimized to improve ion conductivity by introducing large-sized cations, low-valent cations and high-valent anions into the oxide solid electrolyte.
Ultra-high ionic conductivity exceeding 1 mS cm-1 at room temperature is achieved, and the performance and efficiency of the electrolyte are improved.
Smart Images

Figure CN119812449A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid electrolyte technology, and in particular to an oxide solid electrolyte and a preparation method thereof, and an all-solid-state battery. Background Art
[0002] Compared with the electrolyte in traditional liquid lithium batteries, solid electrolytes not only have the function of transmitting lithium ions, but also act as a separator to prevent battery short circuit. After decades of research and development, solid electrolytes (SSE) are divided into three categories: inorganic solid electrolytes (ISE), solid polymer electrolytes (SPE) and composite polymer electrolytes (CPE), and solid inorganic electrolytes include halide solid electrolytes, sulfide solid electrolytes and oxide solid electrolytes.
[0003] Currently reported oxide SSEs include garnet, LISICON, NASICON and other materials. Among them, LATP, as a NASICON-type SSE, has been widely studied in solid-state lithium batteries due to its advantages such as non-flammability, high conductivity, wide electrochemical window, and easy processing. However, in the process of preparing LATP, there are major challenges such as unsatisfactory phase purity, low sintering activity, high production cost, and ionic conductivity. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing an oxide solid electrolyte and a preparation method thereof, and an all-solid-state battery to improve the ionic conductivity of the oxide solid electrolyte.
[0005] The embodiment of the present application is implemented as follows:
[0006] In a first aspect, the present invention provides an oxide solid electrolyte, the chemical formula of which is A a-b M b X c Ti 2-c Z d P 3-d O e , wherein a=1-2, b=0-1, c=0-1, d=0-1.5, and e=(12-d)-12; A includes any one of Li, Na, and K elements; M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba elements; X includes one or more of Al, Ga, In, La, Y, Sc, Fe, and Cr elements; Z includes one or more of B, S, Si, V, Tc, Re, As, Xe, W, Se, Nb, and Mn elements; wherein A and M are different, and b, c, and d are not 0 at the same time.
[0007] This application is through a variety of functional ion pairs Aa-b M b X c Ti 2-c Z d P 3-d O 12 Doping modification is performed on key lattice sites, including using large-size cations (M ions) to partially replace Li, Na or K ions, using low-valent cations (X ions) to partially replace Ti ions, and using other polyanions (Z and O complexes) to partially replace PO4 3- , achieving multi-ion co-doping synergistic effect can further improve ionic conductivity. Among them, introducing ions with larger atomic radius (such as Na + , K + etc.), which can effectively increase the lattice constant to Li + It provides a wider diffusion channel, thereby reducing the migration energy barrier of ions and promoting Li + Rapid migration in the electrolyte; using low-valent cations (such as Al 3+ , Ga 3+ By replacing Ti ions with other polyanions (such as BO3 3- 、SiO4 4- 、SO4 4- etc.) partially replace the traditional -3 valent PO4 3- , which not only increases the concentration of Li or Na in the lattice, but also enhances the stability of the crystal structure and improves the ionic conductivity due to the introduction of high-valent anions. Therefore, the oxide solid electrolyte provided by the present application achieves a conductivity of more than 1 mS cm at room temperature through the synergistic effect of multi-ion doping. -1 Ultra-high ionic conductivity.
[0008] In some embodiments of the present application, the chemical formula of the oxide solid electrolyte is Li a-b M b X c Ti 2-c Z d P 3-d O 12 , wherein M includes one or more of Na, K, Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of S, Si, V, Nb, W, Se and Mn; or, the chemical formula of the oxide solid electrolyte is Li a-b M b X c Ti 2-c Zd P 3-d O 12-d , wherein Z includes B; or, the chemical formula of the oxide solid electrolyte is Na a-b M b X c Ti 2-c Z d P 3-d O 12 , wherein M includes one or more of K, Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of B, S, Si, V, Nb, W, Se and Mn; or, the chemical formula of the oxide solid electrolyte is Na a-b M b X c Ti 2-c Z d P 3-d O 12-d , wherein Z includes B; or, the chemical formula of the oxide solid electrolyte is K a-b M b X c Ti 2-c Z d P 3-d O 12 , wherein M includes one or more of Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of B, S, Si, V, Nb, W, Se and Mn; or, the chemical formula of the oxide solid electrolyte is K a-b M b X c Ti 2-c Z d P 3- d O 12-d , where Z includes B.
[0009] The oxide solid electrolyte provided in the present application includes a Li source electrolyte, a Na source electrolyte and a K source electrolyte, and the chemical formulas thereof are Li a-b M b X c Ti 2-c Z d P 3-d O 12 、Na a-b M b X c Ti 2-c Z d P 3-d O12 and K a-b M b X c Ti 2-c Z d P 3-d O 12 In the above electrolytes, large cations (such as Na + , K + etc.) to partially replace Li, Na or K ions, and use low-valent cations (such as Al 3+ , Ga 3+ etc.) to partially replace Ti ions and utilize other polyanions (such as BO3 3- 、SiO4 4- 、SO4 4- etc.) partially replace PO4 3- , achieving the synergistic effect of multi-ion co-doping can further improve the ionic conductivity.
[0010] In some embodiments of the present application, the oxide solid electrolyte includes Li a Al c Ti 2-c (PO4) 3-d (ZO4) d 、Na a Al c Ti 2-c (PO4) 3-d (ZO4) d and K a Al c Ti 2-c (PO4) 3-d (ZO4) d Any one of the following, wherein a=1-2, c=0-1, d=0-1.5, and Z includes one or more of S, Si, V, and Nb elements; or the oxide solid electrolyte includes Li a Al c Ti 2-c (PO4) 3-d (ZO3) d 、Na a Al c Ti 2-c (PO4) 3-d (ZO3) d and K a Al c Ti 2-c (PO4) 3-d (ZO3) d Any one of the following; wherein, a=1~2, c=0.5~1, d=0.15~1.5, and Z includes B.
[0011] In some embodiments of the present application, the oxide solid electrolyte includes Li 1.44 Al 0.5 Ti 1.5 (PO4) 2.94 (SO4) 0.06 , Li 1.35 Al 0.5 Ti 1.5 (PO4) 2.85 (SO4) 0.15 , Li 1.51 Al 0.5 Ti 1.5 (PO4) 2.99 (SiO4) 0.01 , Li 1.53 Al 0.5 Ti 1.5 (PO4) 2.97 (SiO4) 0.03 , Li 1.55 Al 0.5 Ti 1.5 (PO4) 2.95 (SiO4) 0.05 , Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4) 2.85 (BO3) 0.15 and Li 1.5 Al 0.5 Ti 1.5 (PO4) 2.95 (BO3) 0.05 Any one of .
[0012] In a second aspect, the present invention provides a method for preparing an oxide solid electrolyte, comprising: mixing a titanium source compound with a catalyst to obtain a TiO 2+ The complexing agent, A2CO3, M source compound, X source compound, NH4H2PO4 and Z source compound are then added to the TiO 2+ The solution is stirred to form a sol; the sol is dried and then ball milled, formed and sintered in sequence to obtain an oxide solid electrolyte;
[0013] Among them, the M source compound includes MCO3, the X source compound includes XNO3, and the Z source compound includes AZO4 and / or H3BO3, wherein A includes any one of Li, Na and K elements; M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr and Ba elements; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr elements; Z includes one or more of S, B, Si, V, Tc, Re, As, Xe, W, Se, Nb and Mn elements.
[0014] The present invention is to mix a titanium source compound with a catalyst to obtain a titanium-containing 2+ The complexing agent, A2CO3, M source compound, X source compound, NH4H2PO4 and Z source compound are then added to the TiO 2+ In the solution, stirring forms a sol. In this process, the components are evenly mixed to form a uniform sol. Then, through steps such as ball milling and sintering, the microstructure of the electrolyte material is adjusted to form a nanostructure with a high specific surface area, thereby preparing an oxide solid electrolyte material with high ionic conductivity. In other words, the present application prepares the electrolyte material by the sol-gel method, which can achieve uniform mixing of the components, effectively control the microstructure of the material, form a nanostructure with a high specific surface area, and further improve the ionic conductivity of the electrolyte.
[0015] In some embodiments of the present application, the titanium source compound includes C 12 H 28 O4Ti."
[0016] C 12 H 28 O4Ti is a titanium source compound. Its good solubility in organic solvents enables it to form a uniform solution. It also has high reactivity and can quickly generate high-purity and high-quality titanium oxide under relatively mild conditions, thereby improving the ionic conductivity of the solid electrolyte.
[0017] In some embodiments of the present application, the catalyst includes HNO3.
[0018] HNO3 as a catalyst can effectively increase the reaction rate, promote the conversion of titanium source compounds, and promote the generation of purer and more uniform TiO 2+ solution; it can also enhance the stability and uniformity of the sol and promote the formation of high-quality sol.
[0019] In some embodiments of the present application, the complexing agent includes citric acid.
[0020] As a polycarboxylic acid, citric acid has good complexing ability and can effectively form stable complexes with metal ions (such as titanium, aluminum, etc.). By complexing with metal ions, citric acid can affect the crystal structure and phase composition of the material during the sintering process, thereby improving the ionic conductivity.
[0021] In some embodiments of the present application, drying includes: a drying temperature of 100-150° C. and a drying time of 12-24 hours.
[0022] Within the above temperature and time range, the water and other volatile solvents in the sol can be effectively removed, and the material can be dried evenly.
[0023] In some embodiments of the present application, ball milling includes: a mass ratio of ball milling raw materials to ball milling beads is 1:(5-10); and / or a ball milling speed is 300-400 r / min, and a ball milling time is 24-48 h.
[0024] In some embodiments of the present application, sintering includes: heating to 550-600°C at a heating rate of 5-10°C / min, keeping the temperature for 1-3 hours, then continuing to heat to 950-1050°C, keeping the temperature for 5-6 hours, and then cooling naturally.
[0025] Setting the mass ratio of ball milling raw materials to ball milling beads to 1:(5-10), the ball milling speed to 300-400r / min and the ball milling time to 24-48h can effectively improve the fineness and uniformity, effectively control the morphology and size distribution of the particles, promote the interaction between materials, reduce impurities and agglomeration, and improve the physical and chemical properties.
[0026] In a third aspect, an embodiment of the present application provides an all-solid-state battery, comprising any of the above-mentioned oxide solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped with SO4 2- XRD patterns before and after;
[0029] Figure 2 The powder sample Li prepared in Example 2 of the present application 1.35Al 0.5 Ti 1.5 (PO4) 2.85 (SO4) 0.15 SEM images and EDS element analysis;
[0030] Figure 3 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped SiO4 4- XRD patterns before and after;
[0031] Figure 4 LiTi2(PO4)3 doped with Al 3+ XRD patterns before and after;
[0032] Figure 5 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped with SO4 2- Room temperature electrochemical impedance spectroscopy before and after;
[0033] Figure 6 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped SiO4 4- Room temperature electrochemical impedance spectroscopy before and after;
[0034] Figure 7 LiTi2(PO4)3 doped with Al 3+ Room temperature electrochemical impedance spectroscopy before and after. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] The following is a detailed description of an oxide solid electrolyte and a preparation method thereof, and an all-solid-state battery according to an embodiment of the present application.
[0037] The present invention provides an oxide solid electrolyte having a chemical formula of A a-b M b X c Ti 2-c Z d P 3-d O e, wherein a=1-2, b=0-1, c=0-1, d=0-1.5, and e=(12-d)-12; A includes any one of Li, Na, and K elements; M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, and Ba elements; X includes one or more of Al, Ga, In, La, Y, Sc, Fe, and Cr elements; Z includes one or more of B, S, Si, V, Tc, Re, As, Xe, W, Se, Nb, and Mn elements; wherein A and M are different, and b, c, and d are not 0 at the same time.
[0038] The present invention can effectively increase the lattice constant of Li by: 1. Introducing ions with larger atomic radius (such as Na, K, etc.) at the Li position + It provides a wider diffusion channel, thereby reducing the migration energy barrier of ions and promoting Li + 1. Rapid migration in the electrolyte; 2. Use low-valent cations (such as Al, Ga, etc.) to partially replace Ti ions, increase the concentration of Li or Na vacancies in the lattice, accelerate the migration rate of lithium ions, and further improve ionic conductivity; 3. By using other polyanions with -3, -4 or -5 valence (such as BO3 3- 、SiO4 4- 、SO4 4- etc.) partially replace the traditional -3 valent PO4 3- , which not only increases the concentration of Li or Na in the lattice, but also enhances the stability of the crystal structure and improves the ionic conductivity due to the introduction of high-valent anions; that is, through the synergistic effect of multi-ion doping, it has a conductivity of more than 1 mS cm at room temperature. -1 Ultra-high ionic conductivity.
[0039] Among them, when A is Li, Na and K respectively, the chemical formula of the oxide solid electrolyte is Li a- b M b X c Ti 2-c Z d P 3-d O 12 、Na a-b M b X c Ti 2-c Z d P 3-d O 12 and K a-b M b X c Ti 2-c Z d P 3-d O 12, wherein M includes one or more of K, Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of S, Si, V, Nb, W, Se and Mn; or, when A is Li, Na and K respectively, the chemical formula of the oxide solid electrolyte is Li a-b M b X c Ti 2-c Z d P 3-d O 12-d 、Na a-b M b X c Ti 2-c Z d P 3-d O 12-d and K a-b M b X c Ti 2-c Z d P 3- d O 12-d , Z includes B.
[0040] As an example, the oxide solid electrolyte includes Li a Al c Ti 2-c (PO4) 3-d (ZO4) d 、Na a Al c Ti 2-c (PO4) 3-d (ZO4) d and K a Al c Ti 2-c (PO4) 3-d (ZO4) d Any one of; wherein a=1-2, c=0-1, d=0-1.5, Z includes one or more of S, Si, V and Nb elements; or the oxide solid electrolyte includes Li a Al c Ti 2-c (PO4) 3-d (ZO3) d 、Na a Al c Ti 2-c (PO4) 3-d (ZO3) d and K a Al c Ti2-c (PO4) 3-d (ZO3) d Any one of the following, wherein a=1~2, c=0~1, d=0~1.5, and Z includes B.
[0041] Specifically, as an example, the oxide solid electrolyte includes Li 1.44 Al 0.5 Ti 1.5 (PO4) 2.94 (SO4) 0.06 , Li 1.35 Al 0.5 Ti 1.5 (PO4) 2.85 (SO4) 0.15 , Li 1.51 Al 0.5 Ti 1.5 (PO4) 2.99 (SiO4) 0.01 , Li 1.53 Al 0.5 Ti 1.5 (PO4) 2.97 (SiO4) 0.03 , Li 1.55 Al 0.5 Ti 1.5 (PO4) 2.95 (SiO4) 0.05 , Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4) 2.85 (BO3) 0.15 and Li 1.5 Al 0.5 Ti 1.5 (PO4) 2.95 (BO3) 0.05 Any one of .
[0042] The preparation method of the above-mentioned oxide solid electrolyte is described below.
[0043] A method for preparing an oxide solid electrolyte comprises: mixing a titanium source compound with a catalyst to react to obtain a TiO 2+ The complexing agent, A2CO3, M source compound, X source compound, NH4H2PO4 and Z source compound are then added to the TiO 2+a solution of 400 μm and a mixture of 400 μm and 500 μm, stirring to form a sol; drying the sol and then sequentially performing ball milling, molding and sintering to obtain an oxide solid electrolyte; wherein the M source compound comprises MCO3, the X source compound comprises XNO3, and the Z source compound comprises AZO4 and / or H3BO3, wherein A comprises any one of Li, Na and K elements; M comprises one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr and Ba elements; X comprises one or more of Al, Ga, In, La, Y, Sc, Fe and Cr elements; and Z comprises one or more of S, Si, V, Tc, Re, As, Xe, W, Se, Nb and Mn elements.
[0044] In the preparation method, a titanium source compound is reacted with a catalyst to generate a 2+ A solution is prepared, and a complexing agent and other compounds are added, stirred and mixed to form a uniform sol, and the sol is then subjected to ball milling and sintering treatments to obtain an oxide solid electrolyte material with high ionic conductivity. Therefore, the present application prepares the electrolyte material by the sol-gel method, which can achieve uniform mixing of the components on the one hand, and effectively control the microstructure of the material on the other hand, forming a nanostructure with a high specific surface area, thereby increasing the migration rate of lithium ions and further improving the ionic conductivity.
[0045] Among them, titanium source compounds include but are not limited to C 12 H 28 O4Ti; the catalyst includes but is not limited to HNO3; the complexing agent includes but is not limited to citric acid.
[0046] As an example, Li a-b M b X c Ti 2-c Z d P 3-d O 12 The preparation method comprises the following steps:
[0047] C 12 H 28 O4Ti is added to deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, a small amount of deionized water is added to the Ti(OH)4 precipitate, and an appropriate amount of concentrated HNO3 is added to generate TiO 2+, after the precipitate is completely dissolved, immediately add citric acid stabilizing solution. Then add Na2CO3, MCO3, XNO3, stir until completely dissolved, then add NH4H2PO4, NaZO4, stir for half an hour to form a sol. Then dry at 100-150℃ for 12-24h, put the dried material into a ball mill with a material bead ratio of 1:(5-10) and add an appropriate amount of alcohol for wet ball milling, and set the parameters to 300-400r / min and 24-48h. After that, the ball-milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 550-600℃ at a heating rate of 5-10℃ / min, and kept warm for 1-3h, and then continued to heat to 950-1050℃, kept warm for 5-6h, and then cooled naturally to obtain the target product.
[0048] As an example, Na a-b M b X c Ti 2-c Z d P 3-d O 12 The preparation method comprises the following steps:
[0049] C 12 H 28 O4Ti is added to deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, a small amount of deionized water is added to the Ti(OH)4 precipitate, and an appropriate amount of concentrated HNO3 is added to generate TiO 2+ , after the precipitate is completely dissolved, immediately add citric acid stabilizing solution. Then add Na2CO3, MCO3, XNO3, stir until completely dissolved, then add NH4H2PO4, NaZO4, stir for half an hour to form a sol. Then dry at 100-150℃ for 12-24h, put the dried material into a ball mill with a material bead ratio of 1:(5-10) and add an appropriate amount of alcohol for wet ball milling, and set the parameters to 300-400r / min and 24-48h. After that, the ball-milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 550-600℃ at a heating rate of 5-10℃ / min, and kept warm for 1-3h, and then continued to heat to 950-1050℃, kept warm for 5-6h, and then cooled naturally to obtain the target product.
[0050] As an example, K a-b M b X c Ti 2-c Z d P 3-d O 12 The preparation method comprises the following steps:
[0051] C 12 H 28 O4Ti is added to deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, a small amount of deionized water is added to the Ti(OH)4 precipitate, and an appropriate amount of concentrated HNO3 is added to generate TiO 2+ , after the precipitate is completely dissolved, immediately add citric acid stabilizing solution. Then add K2CO3, MCO3, XNO3, stir until completely dissolved, then add NH4H2PO4, KZO4, stir for half an hour to form a sol. Then dry at 100-150℃ for 12-24h, put the dried material into a ball mill with a material-bead ratio of 1:(5-10) and add an appropriate amount of alcohol for wet ball milling, and set the parameters to 300-400r / min and 24-48h. After that, the ball-milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 550-600℃ at a heating rate of 5-10℃ / min, and kept warm for 1-3h, and then continued to heat to 950-1050℃, kept warm for 5-6h, and then naturally cooled to obtain the target product.
[0052] Wherein, as an example, MCO3 includes but is not limited to Na2CO3, K2CO3, Rb2CO3, Cs2CO3, BeCO3, MgCO3, CaCO3, SrCO3, BaCO3. XNO3 includes but is not limited to Al(NO3)3, Ga(NO3)3, In(NO3)3, La(NO3)3, Y(NO3)3, Sc(NO3)3, Fe(NO3)3. LiZO4 includes but is not limited to Li2SO4, Li4SiO4, Li3VO4, LiTcO4, Li2ReO4, Li3AsO4, LiXeO4, Li2WO4, Li2SeO4, LiMn2O4.
[0053] The features and performance of the present application are further described in detail below in conjunction with the embodiments.
[0054] Example 1
[0055] This embodiment provides an oxide solid electrolyte, whose chemical formula is Li 1.44 Al 0.5 Ti 1.5 (PO4) 2.94 (SO4) 0.06 , and its preparation method comprises the following steps:
[0056] 2.8 g of C 12 H 28O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 8mL of deionized water was added to the Ti(OH)4 precipitate, and 1.75mL of concentrated HNO3 was added to generate TiO 2+ , after the precipitate is completely dissolved, 4.3g of citric acid stabilizing solution is immediately added. Then 0.37g of Li2CO3 and 1.23g of Al(NO3)3·9H2O are added, and after stirring and completely dissolved, 2.22g of NH4H2PO4 and 0.043g of Li2SO4 are added, and a sol is formed after stirring for half an hour; then dried at 150℃ for 12h, the dried material is placed in a ball mill with a material-bead ratio of 1:10 and an appropriate amount of alcohol for wet ball milling, the ball milling speed is 400r / min, and the ball milling time is 24h; then the ball milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 600℃ at a heating rate of 10℃ / min, and the temperature is kept for 1h, and then the temperature is continued to rise to 950℃, and the temperature is naturally lowered after 5h of keeping the temperature to obtain the target product.
[0057] Example 2
[0058] This embodiment provides an oxide solid electrolyte, whose chemical formula is Li 1.35 Al 0.5 Ti 1.5 (PO4) 2.85 (SO4) 0.15 , and its preparation method comprises the following steps:
[0059] 2.8 g of C 12 H 28 O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 8mL of deionized water was added to the Ti(OH)4 precipitate, and 1.75mL of concentrated HNO3 was added to generate TiO 2+ , after the precipitate is completely dissolved, 4.3g of citric acid stabilizing solution is immediately added. Then 0.324g of Li2CO3 and 1.23g of Al(NO3)3·9H2O are added, and after stirring and completely dissolved, 2.15g of NH4H2PO4 and 0.108g of Li2SO4 are added, and a sol is formed after stirring for half an hour; then dried at 150℃ for 12h, the dried material is placed in a ball mill with a material-bead ratio of 1:10 and an appropriate amount of alcohol for wet ball milling, the ball milling speed is 400r / min, and the ball milling time is 24h; then the ball milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 600℃ at a heating rate of 10℃ / min, and the temperature is kept for 1h, and then the temperature is continued to rise to 950℃, and the temperature is naturally lowered after 5h of keeping the temperature to obtain the target product.
[0060] Example 3
[0061] This embodiment provides an oxide solid electrolyte, whose chemical formula is Li 1.51 Al 0.5 Ti 1.5 (PO4) 2.99 (SiO4) 0.01 , and its preparation method comprises the following steps:
[0062] 2.8 g of C 12 H 28 O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 8mL of deionized water was added to the Ti(OH)4 precipitate, and 1.75mL of concentrated HNO3 was added to generate TiO 2+ , after the precipitate is completely dissolved, immediately add 4.3g of citric acid stabilizing solution. Then add 0.392g of Li2CO3 and 1.23g of Al(NO3)3·9H2O, stir and dissolve completely, then add 2.258g of NH4H2PO4 and 0.0079g of Li4SiO4, stir for half an hour to form a sol. Then dry at 150℃ for 12h, put the dried material into a ball mill with a material-bead ratio of 1:10 and add appropriate amount of alcohol for wet ball milling, the parameters are set to 400rpm and 24h. After that, the ball-milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 600℃ at a heating rate of 10℃ / min, kept warm for 1h, and then continued to heat to 950℃, kept warm for 5h, and then naturally cooled to obtain the target product.
[0063] Example 4
[0064] This embodiment provides an oxide solid electrolyte, whose chemical formula is Li 1.53 Al 0.5 Ti 1.5 (PO4) 2.97 (SiO4) 0.03 , and its preparation method comprises the following steps:
[0065] 2.8 g of C 12 H 28 O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 8mL of deionized water was added to the Ti(OH)4 precipitate, and 1.75mL of concentrated HNO3 was added to generate TiO 2+, after the precipitate is completely dissolved, immediately add 4.3g of citric acid stabilizing solution. Then add 0.376g of Li2CO3 and 1.23g of Al(NO3)3·9H2O, stir and dissolve completely, then add 2.243g of NH4H2PO4 and 0.0236g of Li4SiO4, stir for half an hour to form a sol. Then dry at 150℃ for 12h, put the dried material into a ball mill with a material-bead ratio of 1:10 and add appropriate amount of alcohol for wet ball milling, the parameters are set to 400rpm and 24h. After that, the ball-milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is raised to 600℃ at a heating rate of 10℃ / min, kept warm for 1h, and then continued to heat to 950℃, kept warm for 5h, and then naturally cooled to obtain the target product.
[0066] Example 5
[0067] This embodiment provides an oxide solid electrolyte, whose chemical formula is Li 1.55 Al 0.5 Ti 1.5 (PO4) 2.95 (SiO4) 0.05 , and its preparation method comprises the following steps:
[0068] 2.8 g of C 12 H 28 O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 8mL of deionized water was added to the Ti(OH)4 precipitate, and 1.75mL of concentrated HNO3 was added to generate TiO 2+ , after the precipitate is completely dissolved, immediately add 4.3g of citric acid stabilizing solution. Then add 0.36g of Li2CO3 and 1.23g of Al(NO3)3·9H2O, stir and dissolve completely, then add 2.228g of NH4H2PO4 and 0.039g of Li4SiO4, stir for half an hour to form a sol. Then dry at 150℃ for 12h, put the dried material into a ball mill with a material-bead ratio of 1:10 and add appropriate amount of alcohol for wet ball milling, the parameters are set to 400rpm and 24h. After that, the ball-milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, heated to 600℃ at a heating rate of 10℃ / min, kept warm for 1h, and then continued to heat to 950℃, kept warm for 5h and naturally cooled to obtain the target product.
[0069] Example 6
[0070] This embodiment provides an oxide solid electrolyte, whose chemical formula is Li 1.5 Al 0.5 Ti 1.5(PO4)3, the preparation method thereof comprises the following steps:
[0071] 2.8 g of C 12 H 28 O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 8mL of deionized water was added to the Ti(OH)4 precipitate, and 1.75mL of concentrated HNO3 was added to generate TiO 2+ After the precipitate is completely dissolved, 4.3g of citric acid stabilizing solution is immediately added. Then 0.4g of Li2CO3 and 1.23g of Al(NO3)3·9H2O are added, and after stirring and completely dissolved, 2.267g of NH4H2PO4 is added, and a sol is formed after stirring for half an hour; then dried at 150℃ for 12h, the dried material is placed in a ball mill with a material-bead ratio of 1:10 and an appropriate amount of alcohol for wet ball milling, the ball milling speed is 400r / min, and the ball milling time is 24h; then the ball milled sample is dried, ground and pressed, and the pressed piece is placed in an alumina crucible and sintered in a muffle furnace, and the temperature is increased to 600℃ at a heating rate of 10℃ / min, and the temperature is kept for 1h, and then the temperature is continued to be increased to 950℃, and the temperature is naturally reduced after being kept for 5h to obtain the target product.
[0072] Comparative Example
[0073] This comparative example provides an oxide solid electrolyte, whose chemical formula is LiTi2(PO4)3, and whose preparation method comprises the following steps:
[0074] 3.73 g of C 12 H 28 O4Ti was added to 18mL of deionized water and stirred to generate Ti(OH)4 precipitate immediately. After washing and filtering, 11mL of deionized water was added to the Ti(OH)4 precipitate, and 2.33mL of concentrated HNO3 was added to generate TiO 2+ , after the precipitate is completely dissolved, immediately add 5.7g of citric acid stabilizing solution. Then add 0.27g of Li2CO3, stir and dissolve completely, then add 2.267g of NH4H2PO4, stir for half an hour to form a sol; then dry at 150℃ for 12h, put the dried material into a ball mill with a material-bead ratio of 1:10 and add appropriate amount of alcohol for wet ball milling, the ball milling speed is 400r / min, and the ball milling time is 24h; then dry the ball milled sample, grind and press it into a sheet, place the pressed sheet in an alumina crucible, and sinter it in a muffle furnace, heat it to 600℃ at a heating rate of 10℃ / min, keep it for 1h, then continue to heat it to 950℃, keep it for 5h, and then cool it naturally to obtain the target product.
[0075] The preparation methods of the above-mentioned embodiment and comparative example are basically the same, except that different oxide solid electrolytes are prepared. Please see Table 1 for some parameters.
[0076] Table 1
[0077] Group Oxide solid electrolyte Example 1 <![CDATA[Li 1.44 Al 0.5 You 1.5 (PO4) 2.94 (SO4) 0.06 ]]> Example 2 <![CDATA[Li 1.35 Al 0.5 You 1.5 (PO4) 2.85 (SO4) 0.15 ]]> Example 3 <![CDATA[Li 1.51 Al 0.5 The 1.5 (PO4) 2.99 (SiO4) 0.01 ]]> Example 4 <![CDATA[Li 1.53 Al 0.5 The 1.5 (PO4) 2.97 (SiO4) 0.03 ]]> Example 5 <![CDATA[Li 1.55 Al 0.5 The 1.5 (PO4) 2.95 (SiO4) 0.05 ]]> Example 6 <![CDATA[Li 1.5 Al 0.5 Of 1.5 (PO4)3]]> Comparative Example <![CDATA[LiTi2(PO4)3]]>
[0078] Test Example 1
[0079] 1. In this test example, the oxide solid electrolytes prepared in Examples 1-2 and 6 were subjected to molecular structure detection respectively. Figure 1 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped with SO4 2- XRD patterns before and after Figure 2 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped SiO4 4- Please refer to the XRD patterns before and after Figure 1 and Figure 2 .
[0080] from Figure 1 It can be seen that by comparing the XRD diffraction peak positions of the doped sample and the original sample, we can see that the doped SO4 2- This causes the diffraction peaks to shift toward a larger 2θ direction, and as the doping ratio increases, the diffraction peaks shift more. This is because SO4 2- The ionic radius is smaller than that of PO4 3- The ionic radius of SO4 2- Replace PO4 3- When the position is changed, the unit cell parameters will become smaller, thereby increasing 2θ, and the corresponding diffraction peak will shift in the direction of larger 2θ.
[0081] from Figure 2 EDS elemental analysis shows that there is a uniform distribution of S elements inside the sample, proving that SO4 2- Successfully doped with Li 1.5 Al 0.5 Ti 1.5 (PO4)3 inside.
[0082] Figure 3 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped SiO4 4- Please refer to the XRD patterns before and after Figure 3 By comparing the XRD diffraction peak positions of the doped sample and the original sample, it can be seen that the doped SiO4 4-This causes the diffraction peaks to shift toward a smaller 2θ direction, and as the doping ratio increases, the diffraction peaks shift more. This is because SiO4 4- The ionic radius is larger than that of PO4 3- The ionic radius of SiO4 4- Replace PO4 3- When the position is changed, the unit cell parameter will become larger, thereby making 2θ smaller, and the corresponding diffraction peak will shift to the direction where 2θ is smaller.
[0083] Figure 4 LiTi2(PO4)3 doped with Al 3+ Please refer to the XRD patterns before and after Figure 4 By comparing the XRD diffraction peak positions of the doped sample and the original sample, it can be seen that the Al-doped 3+ This causes the diffraction peaks to shift toward a larger 2θ direction, and as the doping ratio increases, the diffraction peaks shift more. This is because Al 3+ The ionic radius is smaller than that of Ti 4+ The ionic radius of Al 3+ Replace Ti 4+ When the position is changed, the unit cell parameters will become smaller, thereby increasing 2θ, and the corresponding diffraction peak will shift in the direction of larger 2θ.
[0084] Test Example 2
[0085] 1. This test example The oxide solid electrolytes prepared in Examples 1-6 and Comparative Examples were tested for ionic conductivity and electrochemical impedance spectroscopy.
[0086] Among them, ionic conductivity measurement: In the temperature range of 25-120℃, every 20℃ is used as a data collection point to perform an AC impedance spectroscopy (EIS) test on the solid electrolyte. After the temperature changes, the test mold needs to be kept warm for 1 hour to ensure that the electrolyte temperature is stable. After measuring the impedance of the solid electrolyte, its ionic conductivity at different temperatures is calculated according to formula 1-1:
[0087]
[0088] Where σ is the ionic conductivity (S cm -1 ), d and S are the thickness (cm) and area (cm) of the solid electrolyte sheet, respectively. 2 ), Z is the measured total electrolyte impedance (Ω). After obtaining the lithium ion conductivity of the solid electrolyte at different temperatures, the activation energy of lithium ion conduction can be calculated using Arrhenius formula 1-2:
[0089]
[0090] Where E ais the activation energy of lithium ion conduction, A0 is a constant, k is the Boltzmann constant, and T is the temperature (K).
[0091] Electrochemical impedance measurement: Electrochemical AC impedance spectroscopy is a common technique for measuring the impedance of solid electrolytes. It mainly applies small AC potential waves of different frequencies to both sides of the solid electrolyte and measures the change of the phase angle of the impedance with the frequency of the sine wave to obtain impedance spectra of different frequencies. The results of the impedance measurement are displayed through the Nyquist diagram, where the x-axis represents the real part of the impedance and the y-axis represents the absolute value of the imaginary part of the impedance. The impedance Z(w) is shown by formula 1-3:
[0092] Z(w)=Z Re -jZ Im (1-3)
[0093] Where Z Re is the real part of impedance, Z Im is the imaginary part of impedance, and j represents the phase factor. In this experiment, the EC-lab electrochemical workstation produced by Bio-logic in France was used to test the impedance spectrum of the solid electrolyte. The frequency was set to 7Mhz-1hz and the voltage amplitude was 10mV.
[0094] Please see Table 2 for the measurement results of the above items.
[0095] Table 2
[0096]
[0097] As can be seen from Table 2, the present invention uses a variety of functional ions to A a-b M b X c Ti 2-c Z d P 3-d O 12 Doping modification of key lattice sites can significantly improve ionic conductivity and reduce impedance.
[0098] Figure 5 For Li 1.5 Al 0.5 Ti 1.5 (PO4)3 doped with SO4 2- Please refer to the room temperature electrochemical impedance spectroscopy before and after Figure 5 By comparing the electrochemical impedance of the doped sample with that of the original sample, it can be seen that with the increase of SO4 2- As the doping ratio increases, the electrochemical impedance decreases continuously, indicating that SO4 2- Doping can improve ionic conductivity.
[0099] Figure 6 For Li 1.5 Al0.5 Ti 1.5 (PO4)3 doped SiO4 4- Please refer to the room temperature electrochemical impedance spectroscopy before and after Figure 6 By comparing the electrochemical impedance of the doped sample with that of the original sample, it can be seen that as SiO4 4- As the doping ratio increases, the electrochemical impedance decreases continuously, indicating that SiO4 4- Doping can improve ionic conductivity.
[0100] Figure 7 LiTi2(PO4)3 doped with Al 3+ Please refer to the room temperature electrochemical impedance spectroscopy before and after Figure 7 By comparing the electrochemical impedance of the doped sample with that of the original sample, it can be seen that with the increase of Al 3+ As the doping ratio increases, the electrochemical impedance decreases continuously, indicating that Al 3+ Doping can improve ionic conductivity.
[0101] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.
Claims
1. An oxide solid electrolyte, characterized in that: The chemical formula of the oxide solid electrolyte is A a- b M b X c Ti 2-c Z d P 3-d O e , where a=1~2, b=0~1, c=0~1, d=0~1.5, e=(12-d)~12; A includes any one of Li, Na and K elements; M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr and Ba elements; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr elements; Z includes one or more of B, S, Si, V, Tc, Re, As, Xe, W, Se, Nb and Mn elements; Among them, A and M are different, and b, c and d are not 0 at the same time.
2. The oxide solid electrolyte according to claim 1, characterized in that The chemical formula of the oxide solid electrolyte is Li a-b M b X c Ti 2-c Z d P 3-d O 12 , wherein M includes one or more of Na, K, Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of S, Si, V, Nb, W, Se and Mn; or, the chemical formula of the oxide solid electrolyte is Li a-b M b X c Ti 2-c Z d P 3-d O 12-d , where Z includes B; Or, the chemical formula of the oxide solid electrolyte is Na a-b M b X c Ti 2-c Z d P 3-d O 12 , wherein M includes one or more of K, Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of S, Si, V, Nb, W, Se and Mn; or, the chemical formula of the oxide solid electrolyte is Na a- b M b X c Ti 2-c Z d P 3-d O 12-d , where Z includes B; Or, the chemical formula of the oxide solid electrolyte is K a-b M b X c Ti 2-c Z d P 3-d O 12 , wherein M includes one or more of Rb, Cs, Be, Mg and Ca; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr; Z includes one or more of S, Si, V, Nb, W, Se and Mn; or, the chemical formula of the oxide solid electrolyte is K a- b M b X c Ti 2-c Z d P 3-d O 12-d , where Z includes B.
3. The oxide solid electrolyte according to claim 2, characterized in that: The oxide solid electrolyte includes Li a Al c Ti 2-c (PO4) 3-d (ZO4) d 、Na a Al c Ti 2-c (PO4) 3-d (ZO4) d and K a Al c Ti 2-c (PO4) 3-d (ZO4) d Any of the following: Wherein, a=1-2, c=0-1, d=0-1.5, Z includes one or more of S, Si, V and Nb elements; or, the oxide solid electrolyte includes Li a Al c Ti 2-c (PO4) 3-d (ZO3) d 、Na a Al c Ti 2-c (PO4) 3-d (ZO3) d and K a Al c Ti 2-c (PO4) 3-d (ZO3) d Any one of, wherein a=1-2, c=0-1, d=0-1.5, and Z includes B; Optionally, the oxide solid electrolyte includes Li 1.44 Al 0.5 Ti 1.5 (PO4) 2.94 (SO4) 0.06 , Li 1.35 Al 0.5 Ti 1.5 (PO4) 2.85 (SO4) 0.15 , Li 1.51 Al 0.5 Ti 1.5 (PO4) 2.99 (SiO4) 0.01 , Li 1.53 Al 0.5 Ti 1.5 (PO4) 2.97 (SiO4) 0.03 , Li 1.55 Al 0.5 Ti 1.5 (PO4) 2.95 (SiO4) 0.05 , Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4) 2.85 (BO3) 0.15 and Li 1.5 Al 0.5 Ti 1.5 (PO4) 2.95 (BO3) 0.05 Any one of .
4. A method for preparing an oxide solid electrolyte as claimed in any one of claims 1 to 3, characterized in that: include: The titanium source compound is mixed with the catalyst to react to obtain a product containing TiO 2+ The complexing agent, A2CO3, M source compound, X source compound, NH4H2PO4 and Z source compound are then added to the TiO 2+ The solution is stirred to form a sol; After drying the sol, sequentially performing ball milling, molding treatment and sintering to obtain the oxide solid electrolyte; Wherein, the M source compound includes MCO3, the X source compound includes XNO3, and the Z source compound includes AZO4 and / or H3BO3, wherein A includes any one of Li, Na and K elements; M includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr and Ba elements; X includes one or more of Al, Ga, In, La, Y, Sc, Fe and Cr elements; Z includes one or more of S, B, Si, V, Tc, Re, As, Xe, W, Se, Nb and Mn elements.
5. The preparation method according to claim 4, characterized in that: The titanium source compound includes C 12 H 28 O4Ti; Optionally, the catalyst comprises HNO3.
6. The preparation method according to claim 4, characterized in that: The complexing agent includes citric acid.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The drying process includes: a drying temperature of 100-150° C. and a drying time of 12-24 hours.
8. The preparation method according to any one of claims 4 to 6, characterized in that: The ball milling includes: the mass ratio of ball milling raw materials to ball milling beads is 1:(5-10); and / or the ball milling speed is 300-400r / min, and the ball milling time is 24-48h.
9. The preparation method according to any one of claims 4 to 6, characterized in that: The sintering comprises: heating to 550-600° C. at a heating rate of 5-10° C. / min, keeping the temperature for 1-3 hours, then continuing to heat to 950-1050° C., keeping the temperature for 5-6 hours and then cooling naturally.
10. An all-solid-state battery, characterized in that: The invention comprises the oxide solid electrolyte according to any one of claims 1 to 3.
Citation Information
Patent Citations
Solid-state electrolytes for Li batteries and processes for production thereof
CN107078341A
Anion-doped ion conductor material as well as preparation method and application thereof
CN111370755A
Sodium-aluminum-silicon-titanium-phosphorus-oxygen solid electrolyte material and preparation and application methods thereof
CN117855591A
Ultrathin water-based solid electrolyte diaphragm, preparation method and application
CN118888972A
Structured metal electrode and its combination with non-liquid electrolyte
DE102018127787A1
Cited By
Preparation method of solid anode strip with high stability and low interface impedance
CN121076080A